The whitefly Bemisia tabaci (Genn.) (Hemiptera: Aleyrodidae) in processing tomato crop – attack differences among four cultivars - Madeira, João Diogo (2022)
Mestrado em Engenharia Agronómica / Instituto Superior de Agronomia. Universidade de Lisboa